THE RELATIONSHIP BETWEEN ANXIETY LEVELS AND FACING CHILDBIRTH IN THE WORKING AREA OF THE TANGSE HEALTH CENTER, PIDIE REGENCY - Yuliani, Eka; Arlianti, Nopa; Adamy, Aulina (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Anxiety in pregnant women can arise, especially in the third trimester of pregnancy until delivery. During this period, pregnant women feel anxious about various things, such as whether the baby is born normally or not, and the pain that will be felt. As the delivery schedule approaches, especially in the first pregnancy, it is normal for feelings of anxiety to arise. Anxiety during pregnancy can lead to depression due to fear or even trauma if there are problems during labor so that the mother does not want to give birth again. Therefore there is a need to study the behavior of pregnant women in the third trimester with their level of anxiety when facing childbirth in the working area of the Tangse Health Center. Method: This research was conducted using a descriptive- analytical method using a cross- sectional design. The population in this study was 459 pregnant women who were in the working area of the Tangse Health Center. Sampling used purposive sampling technique with a total sample of 80 respondents. Results: The results showed that 24.4% of pregnant women considered themselves not anxious, with 59.8% mild anxiety and 14.6% moderate anxiety. The results of the bivariate analysis show that there is no significant relationship between maternal age (p-value 1.000), maternal education (p-value 0.849), maternal knowledge (p-value 0.196), antenatal care visits (p-value 0.934), and husband's support. (p-value 0.055) with anxiety in facing childbirth in the working area of the Tangse Health Center, Pidie Regency. Recommendation: It is hoped that future researchers will be able to conduct research related to suggestion therapy in pregnant women, and for health workers, it is hoped that health workers will further increase the provision of health information (counseling) regarding pregnancy, especially to primigravida mothers.